Primary School Teacher Performance During The Covid-19 Pandemic - Salma Ida Nasution; Zaka Hadikusuma Ramadan (Universitas Pendidikan Ganesha, 2021)
During the COVID-19 pandemic, the effectiveness of teacher performance can be seen from the quality of teacher performance in implementing online learning involving information and communication technology media. This study aims to analyze more deeply the effectiveness of teacher performance during the covid-19 pandemic in the implementation of online learning. The type of research used is qualitative research. The research subjects were principals, 2 teachers, 2 students, and 2 guardians. The research instruments are observation sheets and interview guidelines. Data collection techniques are interviews and observation. The data analysis technique used the Miles and Huberman model. The results showed that the effectiveness of teacher performance during the COVID-19 pandemic was classified as less effective. The quality of the work of teachers is classified as less effective because of the many obstacles in the implementation of learning during the COVID-19 pandemic. The teacher's punctuality decreases. Teacher initiatives during the pandemic are relatively ineffective. Teachers' ability during the COVID-19 pandemic is classified as less effective due to limited infrastructure, internet quotas, and unstable networks that do not support online learning processes involving technology. Communication during the covid-19 pandemic is classified as less effective because of the many obstacles that cause learning not to take place so that there is no effective communication.